Sonic the Hedgehog [videorecording (Blu-Ray)] - Fowler, Jeff, 1978-; Marsden, James, 1973-; Carrey, Jim, 1962- (Paramount, 2020)
When a small-town sheriff discovers Sonic, a talking hedgehog with amazing abilities, he sets out to save him from the evil Dr. Robotnik.